Corpo, cabelo e consumo : produção simbólica e reprodução cultural entre mulheres negras - Oliveira, Josiane Silva de (2009)
In developing this research, my goal was to understand how the construction of the meanings of consumer goods is aimed specifically at black women in the industry sector of personal hygiene, perfumery and cosmetics, and how these meanings are perceived, constructed or reconstructed through consumption performed by this population. Based on an interpretive approach and anthropological understanding of culture and the phenomenon of consumption, I sought to investigate how the dynamics of Brazilian culture is the cultural representation and reproduction of black women in the study environment as regards, in particular the dynamics of marketing. This process has shown to occur in a dynamic construction that has real effects, both material and symbolic, which position individuals in the world and in the context analyzed here, as a black woman. In this context, I discuss how consumer goods are made up of cultural meanings in this environment, and are used as a mechanism for representation and reproduction of cultural environment in which they are this population and consumer goods are dumped. Therefore, we interviewed eleven women in black period of nineteen of the April and thirty of the July 2009, where the main results of research show the bodies of black women as the locus symbolic and material, where they built the stigmas associated with this population. This also represents the trading strategies of ethnic and racial conflicts in Brazil. In this respect, the consumption, for black women, is a practical and symbolic material that expresses ethnic and social belonging, especially when related to curly hair, because the handling of these reflect the social and ethnic conflicts which these women are constantly involved in Brazilian society, it also constitutes a mechanism of cultural reproduction.